2019
DOI: 10.15255/cabeq.2018.1454
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Cytotoxicity, and Antioxidative Activity of Natural Deep Eutectic Solvents Containing Organic Acid

Abstract: Natural deep eutectic solvents (NADES) may be considered ‘designer solvents’ due to their numerous structural variations and the possibility of tailoring their physicochemical properties. Prior to their industrial application, characterization of NADES is essential, including determination of their physicochemical properties, cytotoxicity, and antioxidative activity. The most important physicochemical properties of eight prepared NADES (choline chloride:malic acid, proline:malic acid, choline chloride:proline:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 24 publications
3
48
0
1
Order By: Relevance
“…The polarity of NADES was determined using Nile red as a solvatochromic probe, as described in Jeong et al (2017). Viscosity was measured according to Mitar et al, (2019).…”
Section: Preparation and Characterization Of The Natural Deep Eutectic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarity of NADES was determined using Nile red as a solvatochromic probe, as described in Jeong et al (2017). Viscosity was measured according to Mitar et al, (2019).…”
Section: Preparation and Characterization Of The Natural Deep Eutectic Solventsmentioning
confidence: 99%
“…On the other side when choline was used as a component of the ready-to-use extract for food fortification, its odour and taste could be unpleasant for consumers (EFSA FEEDAP Panel, 2011;Panić, Radić Stojković, et al, 2019b). Therefore, besides choline-based NADES, we also tested NADES containing betaine as HBA, which have similar characteristics as choline (Mitar, Panić, Kardum, Halambek, & Sander, 2019). For example, comparing the ChCit and BCit, pH value for both of them is < 3, po-larity~50, density~1.2 g cm −3 , EC50 < 2000 mg L −1 and antioxidant capacity~1.5 μmol Trolox equivalent g NADES −1 (Mitar et al, 2019;Panić, Radić Stojković, et al, 2019b).…”
Section: Preparation and Characterization Of Nades-based Extractsmentioning
confidence: 99%
“…The viscosity of DESs represents one of the biggest drawbacks due to a slow mass transfer, but viscosity can be reduced just by adding H 2 O or increasing the extraction temperature [49]. Apart from reducing viscosity, the addition of water and an increase in temperature can affect pH [50], enabling the extraction of compounds over a wider pH range.…”
Section: Comparison Of the Possibility Of Extraction By Dessmentioning
confidence: 99%
“…1 (a that despite resulting in high viscosities, DESs prepared from sugars 15,34a are relatively less toxic to cells than those composed of organic acids. 35,37 It is the cholinium (Ch + ) cations of DESs, which partly dissociate in aqueous solutions, that interact with the charged groups on the surface of the membrane, leading to its disruption. 20,35,36 Further, ternary DESs or DESDs exhibit more toxicity due to the delocalised charges of the hydrogen bonds in comparison with their individual components.…”
Section: Antimicrobial Actionmentioning
confidence: 99%
“…35,37 It is the cholinium (Ch + ) cations of DESs, which partly dissociate in aqueous solutions, that interact with the charged groups on the surface of the membrane, leading to its disruption. 20,35,36 Further, ternary DESs or DESDs exhibit more toxicity due to the delocalised charges of the hydrogen bonds in comparison with their individual components. Recently, research has revealed the enhanced absorption of DESs in the lipid bilayer of animal cells, while their consequence on the microbial membranes is still indenite.…”
Section: Antimicrobial Actionmentioning
confidence: 99%